Analysis Of The Impact Of The Development Of Public And Private Educational Initiatives In The Field Of Investments On The Increase In Investment Activity Of The Population Of Uzbekistan (2020- 2024) (Diversity Research: Journal of Analysis and Trends, 2025)
The article examines the relationship between the development of investment education and the growth of investment activity of citizens of the Republic of Uzbekistan. Special attention is paid to the quantitative and qualitative growth of public and private educational institutions in the field of investment and brokerage activities in the period 2020- 2024. Based on the analysis of statistical and empirical data, the correlation between the availability of educational programs and the increase in private investment in the country's economy is assessed